The use of technetium 99m hexa-methyl propylene amine oxime spect scanning in acute stroke management. - Winterton, Ruth (My University, 1991)
19 patients were selected, from the patients screened, for investigation within 48 hours of the onset of an ischaemic cerebrovascular accident. Clinical neurulogical scoring, computerized tomography lCT) scans and single photon emission computed tomography (SPECT) scans were performed on day 1, day 10 and day 30. SPECT scan data was analysed by 5 semi-quantitative methods, and findings were compared with neuroloyical clinical scores on each respective day. It was found that day 1 SPECT scans are of value for early localization of the acute ischaemic infarction. A multiple regression model was developed using both the day 30 Defect Volume index and segmental analysis score which related to the day 30 clinical scores. The day 1 model was unsatisfactory and no such model was found relating day 10 SPECT semi-quantitative methods to day 10 clinical scoring. Changes in semi-quantitative scores from day 1 to day 30 did not correlate with clinical changes. Longer follow up may be required for there to be value in performing SPECT scans in stroke trials. A prognostic equation was derived by multiple regression analysis of day 1 SPECT scan scores and day 30 clinical scores.
A short report submitted to the Faculty of Medicine, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Medicine in Nuclear Medicine
Keywords: Tomography, Emission-Computed, Single-Photon.; Cerebrovascular Disorders radiography.